Participación de la junta vecinal n° 30 en el fortalecimiento de la seguridad ciudadana de la urbanización libertad, distrito trujillo. 2012 - Otiniano Calderón, Caren Ivette (2013)
This research was conducted with the purpose of knowing the "Participation Neighborhood Board No. 30 in the Public Safety Building on the Urbanisation Libertad, Trujillo District 2011-2012". This research is descriptive in nature and used deductive methods – inductive statistical techniques using observation, interview and survey, with the sampling universe to 60 people. During the study general aspects met Neighborhood Board No. 30 and urbanization Freedom, where they are located, as well as the participation of the neighborhood with other organizations in urbanization: Progress and Development Committee Victor Raul Haya de la Torre, Liberty Traditional Dance Association, Haya sports Club Tower, with which performs work together to improve and implement the Public Safety within the area. Disclosed are various actions that have implemented the Neighborhood Council in its involvement with the neighbors and serenazgo institution which are considered good within the development, and provide peace of mind to the neighbors to walk the streets. It identifies the main difficulties encountered by the Neighborhood Council No. 30 during his tenure as representative of the complex organization Freedom. This information is reflected in the presentation of results and discussion.